2020
DOI: 10.1590/1806-9282.66.8.1087
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with potential cardiovascular and cerebrovascular adverse events in elderly individuals assisted at secondary level

Abstract: SUMMARY OBJECTIVE To identify the use of Potentially Inappropriate Medications with imminent risk of Cardiovascular and Cerebrovascular Adverse Events (PIM-CCVAE), in addition to the factors associated with a group of elderly individuals undergoing therapeutic care in a Brazilian public service. METHODS A cross-sectional retrospective study conducted at a secondary level service located in Carapicuíba, SP, Brasil. Only elderly individuals (≥60 years) who were treated in one of the outpatient departments we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 13 publications
0
8
0
2
Order By: Relevance
“…The 94 studies were conducted across 17 countries. Forty-one studies were conducted in Asia, followed by 22 studies 11, in Europe, 14 studies [79][80][81][82][83][84][85][86][87][88][89][90][91][92] in North America, 8 studies [93][94][95][96][97][98][99][100] in South America, 7 studies [101][102][103][104][105][106][107] in Africa, and 2 studies 108,109 in Oceania. Between 1999 and 2021, a total of 51 studies 11,[37][38][39][40][41][42][79][80][81][82][83][84][85][86][87][88][89][90][91]…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 94 studies were conducted across 17 countries. Forty-one studies were conducted in Asia, followed by 22 studies 11, in Europe, 14 studies [79][80][81][82][83][84][85][86][87][88][89][90][91][92] in North America, 8 studies [93][94][95][96][97][98][99][100] in South America, 7 studies [101][102][103][104][105][106][107] in Africa, and 2 studies 108,109 in Oceania. Between 1999 and 2021, a total of 51 studies 11,[37][38][39][40][41][42][79][80][81][82][83][84][85][86][87][88][89][90][91]…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Between 1999 and 2021, a total of 51 studies 11,[37][38][39][40][41][42][79][80][81][82][83][84][85][86][87][88][89][90][91][92]108,109 were performed in high-income countries, 23 studies [17][18][19][20][21][22][23][24][25][26][27][28][29]77,78,[93][94][95][96][97][98][99][100] in upper-to middle-income countries, 17 studies [30][31][32][33][34][35]…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The study showed that 74.2% of older patients used at least one PIM-CCVAE and were taking daily 1.3 (±1) PIM per older. The most significant factors associated with intake of PIM-CCVAE were found to be the presence of comorbidities, cardiovascular diseases, polypharmacy, and low to moderate morbidity and mortality scores ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…O uso de vários fármacos leva a prática da polifarmácia. A polifarmácia, conceituada como uso concomitante de vários fármacos, a partir de cinco ou mais, favorece a ocorrência de interações medicamentosas (OLIVEIRA et al, 2020) Uma interação ocorre quando um medicamento influencia a ação de outro, podendo ser benéfica quando a associação de fármacos promovem efeitos semelhantes proporcionando uma boa eficácia terapêutica ou redução dos efeitos adversos, entretanto uma interação maléfica pode diminuir a eficácia terapêutica, aumentar excessivamente os efeitos farmacológicos causando toxicidade, acentuar os efeitos colaterais, desenvolver uma reação adversa ao medicamento e até elevar a morbimortalidade (MANSO et al, 2015) .…”
Section: Metodologiaunclassified
“…Tais reações podem exteriorizar-se por precipitação, turvação, floculação e alteração na cor da mistura, contudo, a ausência destas alterações não garante a inexistência da alteração. Os fenômenos físico-químicos compreendem as reações de oxido-redução, inativação de um medicamento por pela incidência da luz, fenômenos de adsorção e neutralização ácido-base (OLIVEIRA et al, 2020).…”
Section: Interações Medicamentosasunclassified